2010
DOI: 10.4269/ajtmh.2010.09-0687
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Protection of Pre-Immunization with Saliva of Long-Term Colonized Phlebotomus papatasi against Experimental Challenge with Leishmania major and Saliva of Wild-Caught P. papatasi

Abstract: Several studies have shown that pre-immunization of mice with needle-injected saliva or pre-exposure to uninfected bites of Phlebotomus papatasi provided protection against infection with Leishmania major , the etiologic agent of zoonotic cutaneous leishmaniasis (ZCL).1-3 These studies were performed by using long-term laboratory colonized sand flies mainly because of the difficulty of working with wild-caught flies. A puzzling fact is that people in leishmaniasis-endemic areas succumb of ZCL despite the high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
14
1
1
Order By: Relevance
“…It is pertinent to mention that the DTH responses in this study were induced by saliva from colony-bred sand flies. Assuming that a T H 1-mediated DTH response in humans correlates with protection against leishmaniasis, our observations differ from those in studies of animal models where colonized sand flies lose the ability to induce the protective immune response generated by wild-caught flies (Laurenti, da Matta et al 2009; Ahmed, Kaabi et al 2010). Additionally, Rohoušová et al (Rohousova, Hostomska et al 2011) reported the loss of saliva-mediated protection from CL in BALB/c mice exposed long-term to a large number of sand fly bites.…”
Section: Discussioncontrasting
confidence: 91%
“…It is pertinent to mention that the DTH responses in this study were induced by saliva from colony-bred sand flies. Assuming that a T H 1-mediated DTH response in humans correlates with protection against leishmaniasis, our observations differ from those in studies of animal models where colonized sand flies lose the ability to induce the protective immune response generated by wild-caught flies (Laurenti, da Matta et al 2009; Ahmed, Kaabi et al 2010). Additionally, Rohoušová et al (Rohousova, Hostomska et al 2011) reported the loss of saliva-mediated protection from CL in BALB/c mice exposed long-term to a large number of sand fly bites.…”
Section: Discussioncontrasting
confidence: 91%
“…Recently it was shown that the colonization of P. papatasi can provide a saliva associated protection. Mice immunized with SGH of F29 labbred female P. papatasi could produce protection against L. major co-inoculated with the same type of SGH while the mice immunized with SGH of the wild-caught sand flies did not produce any protection [33,72,82]. The reason for this may be associated with the different amounts of the salivary proteins in the colonized versus the wild sand flies rather than a genetic variability [42].…”
Section: New Approaches To the Vaccine Developmentmentioning
confidence: 74%
“…The saliva of a sand fly has a composition which helps it to have a successful blood meal and it also helps the parasite to establish in its vertebrate host [28][29][30][31]. The saliva components are not constant in sand flies with different species, sex, age, generation and physiological stages [32][33][34]. Environmental factors and geographical locations seem to affect the saliva composition [35,36].…”
Section: Sand Fly Vector Biologymentioning
confidence: 99%
“…intermedia . There is evidence showing that the immunomodulatory and protective effect of SGS from wild caught and colonized sand flies can vary due to differences in the amount and composition of salivary proteins (Laurenti et al, 2009a, 2009b; Ahmed et al, 2010 and 2016). However, hamsters immunized with wild caught Lu.…”
Section: Discussionmentioning
confidence: 99%